Virgin Coconut Oil and Folic Acid Improve Insulin Signaling and Cardiac Function in Rotenone Induced Stunted Zebrafish Larvae - Syahana Aini; Farica Emiliana; Hanida Aisyah Ardiana; Nurdiana Nurdiana; Ariani Ariani; Brigitta Ida Resita Vebrianti Corebima (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Stunting is a chronic growth disorder caused by prolonged nutritional deficiencies and environmental stress, resulting in reduced height for age. Mitochondrial dysfunction and oxidative stress are increasingly recognized as key contributors to impaired growth and cardiometabolic instability during early development. This study investigated the potential protective effects of Virgin Coconut Oil (VCO) and folic acid on insulin signaling and cardiac finction in a rotenone induced stunted zebrafish larval model. A laboratory experimental study with a true experimental post test only controlled group design was conducted among 30 Zebrafish (Danio rerio) for Irs gene expression at 9 day post fertilization (dpf) as samples per tube, heart rate was measured at 3, 6, and 9 dpf. The total group treatment was five with inclusion and exclusion criterias, negative control (NC), positive control exposed to rotenone (12.5 ppb), VCO treatment (6.25%), folic acid treatment (70 µM), and a combination of VCO and folic acid. Variables assessed in this study included heart rate and insulin receptor substrate (Irs) were evaluated using real time polymerase chain reaction (RT-qPCR) analysis. Data were analyzed using SPSS version 27 for windows. Rotenone significantly reduced Irs expression compared with negative control (0.272 ± 0.128 vc 1.014 ± 0.187; p<0.001). Treatment with VCO (0.678 ± 0.250), folic acid (0.676 ± 0.191), and their combination (0.695 ± 0.231) increased Irs expression relative to the rotenone group (p<0.05), although no significant differences were observed among the treatment groups. Rotenone also elevated heart rate at 9 dpf (236.9 ± 19.2 bpm) compared with the negative control (163.7 ± 10.1 bpm), whereas treatment groups showed improved cardiac parameters. These findings highlight the potential of nutritional interventions targeting mitochondrial oxidative stress to support recovery of insulin signaling and improve metabolic stability in stunting related conditions.